Edukasi Pertolongan Pertama Serangan Jantung - Rebbi Permata Sari, Rebbi; Revi Neini Ikbal (Universitas Alifah Padang, 2024)
One of the causes of death in the world is heart attacks, where the incidence of heart disease is 43.32% with a death rate of 12.91%. In other sources it is also stated that in 2014 people with heart disease in Indonesia numbered 61,682 people and will continue to increase (Bianto et al., 2019). A heart attack is a condition where coronary artery blood flow stops so that the heart muscle experiences a lack of oxygen, causing an infarction. So a heart attack is also called an acute myocardial infarction (AMI). Initial help for a heart attack requires knowledge about good initial aid for a heart attack as a dominant factor which will later be considered important in shaping the individual's actions, in this case helping the victim (Notoatmodjo, 2018). This activity aims to provide education to the public about heart attack first aid education. The methods for implementing this Community Service Program are lectures, discussions and demonstrations. This community service was carried out from October 2023 – February 2024 with a total of 30 participants. The evaluation results showed that there was an increase in knowledge regarding first aid for heart attacks. Suggestions for the community health center are to carry out health education on an ongoing basis.